Mindszenty bíboros az 1956-os forradalom- és szabadságharcban - Bertalan, Péter (Acta Scientiarum Socialium, 2016)
Cardinal Mindszenty in the 1956 Hungarian Revolution and War of Independence.After getting out of prison on the 30th of October 1956, Mindszenty found himself soon in the whirl of revolutionary and political events. The prelate who was freed from his internment in Felsőpetény after long years in captivity probably expected that it would be impossible or very hard to cope with the tasks waiting for him. This explains his seemingly tough resistance towards the intents to free him. His release from prison set in motion the cardinal’s fate-like drift towards his speech of the 3rd of November 1956, which provoked many debates later. He started off from Felsőpetény with military escort, because it was dangerous to get to the capital due to the rapidly changing events. He could experience the enthusiasm of the people and then the direct threat as well when he met the Soviet tanks along the way. The participation of Mindszenty in the political events in the period from the 30th of October to the 3rd of November made the Archbishop of Esztergom an outstanding witness and figure of the history of Hungary of the 20th century.
Keywords: 20th century Hungarian church history; religion and politics; the Catholic Church’s resistance to Communist repression; Peace Priests’ Movement